2015
DOI: 10.1155/2015/932502
|View full text |Cite
|
Sign up to set email alerts
|

Small-World Optimization Algorithm and Its Application in a Sequencing Problem of Painted Body Storage in a Car Company

Abstract: In the car company, the painted body storage (PBS) is set up between the paint shop and the assembly shop. It stores the vehicles in production and reorders the vehicles sequence. To improve production efficiency of assembly shop, a mathematical model is developed aiming at minimizing the consumption rate of options and the total overtime and idle time. As the PBS sequencing process contains upstream sequence inbound and downstream sequence outbound, this paper proposes an algorithm with two phases. In the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…Tabar et al proposed a recognition and sequence optimization method for geometric spot welding in a digital twin environment, which optimized the production sequence of the welding workshop [10]. Tian et al proposed a small-world optimization algorithm and applied it to the resequencing problem between the painting workshop and the assembly workshop [11]. Yilmazlar and Kurz proposed an adaptive local search algorithm for car sequencing problem, and they demonstrated that the algorithm should focus on randomly exploring more non-degenerate solutions rather than spending time accessing degenerate solutions [12].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Tabar et al proposed a recognition and sequence optimization method for geometric spot welding in a digital twin environment, which optimized the production sequence of the welding workshop [10]. Tian et al proposed a small-world optimization algorithm and applied it to the resequencing problem between the painting workshop and the assembly workshop [11]. Yilmazlar and Kurz proposed an adaptive local search algorithm for car sequencing problem, and they demonstrated that the algorithm should focus on randomly exploring more non-degenerate solutions rather than spending time accessing degenerate solutions [12].…”
Section: Related Workmentioning
confidence: 99%
“…The larger the value of HV, the better the solution obtained by the algorithm, and vice versa. The calculation method of HV is shown in Formula (11). In addition, to verify the significance of the differences between algorithms, a Wilcoxon rank-sum test was used to test the significance of the differences between the two algorithms, with a significance level set at 0.05.…”
Section: Parameter Setting and Performance Evaluation Indicatorsmentioning
confidence: 99%
“…SWOA believes that the search process is a basic of information transmission process in search space networks that both operators provided. SWOA was applied in few areas to address optimizations that include network routing problem [244], automobile sequencing problem [245], neural network problem [246]. At the present time of this writing, SWOA is not adopted to any t-way testing strategy.…”
Section: Physic-based Techniquementioning
confidence: 99%
“…Moon et al [15] proposed a storage/retrieval algorithm to simulate the dynamic operation of automobile PBS and verify the proposed system. Tian et al [16] analyzed the scheduling of the PBS sequencing process, which contains upstream sequence inbound and downstream sequence outbound, through a two-stage algorithm. In the first stage, the discrete small-world optimization algorithm (DSWOA) was used to schedule the inbound sequence, and in the second stage, a heuristic algorithm was used to schedule the outbound sequence.…”
Section: Introductionmentioning
confidence: 99%